Community Diagnosis Activity Report in Efforts to Reduce the Incidence of New Stunting Cases in the Working Area of Legok Primary Health Center, Legok Subdistrict, Tangerang Regency, Banten Province - Tomi Wijaya; Wynne Pratiwi; Nadira Rachma Kamila; Emia Debora P; Silviana Tirtasari (Malahayati Nursing Journal, 2025)
ABSTRACT Stunting remains one of Indonesia’s most persistent public health challenges, particularly among children under five. The high incidence of new stunting cases in the working area of Legok Primary Health Center, Tangerang Regency, prompted the implementation of a community diagnosis program to identify its root causes and develop targeted interventions. This program aimed to empower community health cadres as front-line educators to enhance stunting prevention through improved knowledge, skills, and community engagement. The activity was conducted from July 14 to August 16, 2025, and followed a structured community-based diagnostic approach. The problem prioritization process was carried out using the USG (Urgency, Seriousness, Growth) method, while the determinants of health were analyzed through Blum’s Health Field Paradigm. Root cause identification was performed using the non-scoring Delphi technique, Fishbone Diagram, and 5 WHY analysis. These steps revealed that insufficient and inconsistent cadre education on stunting prevention and outdated educational materials were major contributing factors. Interventions included interactive workshops and demonstration-based training sessions focused on balanced nutrition, exclusive breastfeeding, and appropriate complementary feeding practices. The implementation was monitored using the PDCA (Plan-Do-Check-Act) cycle and evaluated through a Systems Approach to ensure quality control and sustainability. A total of 30 community health cadres participated in the intervention. Pre-test results showed that only 2 participants (6.67%) scored above 90, whereas post-test results indicated that all 30 cadres (100%) achieved scores higher than 90. This significant improvement reflects the effectiveness of the training in enhancing cadres’ knowledge and confidence to deliver accurate health education at the community level. This program demonstrated that structured, cadre-centered community education can effectively strengthen local capacity for stunting prevention. Continuous training, active supervision, and integration with maternal and child health programs are essential to sustain knowledge transfer and achieve long-term reductions in stunting prevalence. Keywords: Cadre, Community Diagnosis, Health Education, Stunting Prevention, Training Program.